Inhibitory effects of alkaline extract from the pericarp of Citrus reticulata Blanco on collagen behavior in bleomycin-induced pulmonary fibrosis. (6th April 2021) - Li, Ruo-Fei; Chen, Xin-Yue; Xu, Yong; Feng, Fan-Chao; He, Hai-Lang; Zhou, Xian-Mei
Abstract: Ethnopharmacological relevance: Peel of Citrus reticulata, a Chinese herbal drug with functions of regulating Qi and expelling phlegm, has been used for the treatment of lung related diseases in Chinese medicine for a long time. Its detailed effects on collagen in anti-idiopathic pulmonary fibrosis (IPF) is still unclear. Aim of the study: To explore the effects of citrus alkaline extract (CAE) on collagen synthesis, crosslinking and deposition in pulmonary fibrosis and understand the possible signal pathways involved in the activity. Materials and methods: CAE was prepared from C. reticulata . Bleomycin-induced pulmonary fibrosis mouse model was applied. Pulmonary fibrosis of lung was estimated with histopathology analysis, and collagen deposition was evaluated with immunohistochemistry. Collagen crosslinking related biomarkers and enzymes were analyzed with chemical methods, immunohistochemical and western blot analyses. Results: CAE oral administration lowered hydroxyproline content, inhibited the collagen deposition including expressions of collagen I and III, and relieved bleomycin-induced pulmonary fibrosis in mice model. The productions of a collagen crosslink pyridinoline and crosslinking related enzymes including lysyl oxidase (LOX), lysyl oxidase-like protein 1 (LOXL1) in lung were suppressed by CAE treatment. Furthermore, the protein expressions of TGF-β1 and Smad3 levels in lungs were also downregulated by CAE. Conclusions: This study demonstrated that CAE inhibited collagen synthesis, crosslinking and deposition, and ameliorated bleomycin-induced pulmonary fibrosis. Preliminary mechanism study revealed that CAE exerted its bioactivity at least via downregulation of TGF-β1/Smad3 pathway. Our findings provided a great potential in fighting IPF based on CAE. Graphical abstract: Image 1 Highlights: Citrus alkaline extract (CAE) relieved belomycin-induced pulmonary fibrosis. CAE lowered the collagen synthesis and deposition in fibrotic lung. CAE inhibited the collagen crosslinking related enzymes LOX and LOXL 1. CAE suppressed collagen crosslink pyridinoline. CAE downregulated TGF-β1 and Smad3 signal pathway.